Complete Genome Sequence of the Lignocellulose-Degrading Actinomycete Streptomyces albus CAS922 - Tippelt, Anna (2020)
Streptomyces albus CAS922 was isolated from sunflower seed hulls. Its fully sequenced genome harbors a multitude of genes for carbohydrate-active enzymes, which likely facilitate growth on lignocellulosic biomass. Furthermore, the presence of 27 predicted biosynthetic gene clusters indicates a significant potential for the production of bioactive secondary metabolites.